Redirected Walking Based on Historical User Walking Data - Fan, Cheng-Wei; Xu, Sen-Zhe; Yu, Peng; Zhang, Fang-Lue; Zhang, Song-Hai (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2023)
With redirected walking (RDW) technology, people can explore large virtual worlds in smaller physical spaces. RDW controls the trajectory of the user's walking in the physical space through subtle adjustments, so as to minimize the collision between the user and the physical space. Previous predictive algorithms place constraints on the user's path according to the spatial layouts of the virtual environment and work well when applicable, while reactive algorithms are more general for scenarios involving free exploration or uncon-strained movements. However, even in relatively free environments, we can predict the user's walking to a certain extent by analyzing the user's historical walking data, which can help the decision-making of reactive algorithms. This paper proposes a novel RDW method that improves the effect of real-time unrestricted RDW by analyzing and utilizing the user's historical walking data. In this method, the physical space is discretized by considering the user's location and orientation in the physical space. Using the weighted directed graph obtained from the user's historical walking data, we dynamically update the scores of different reachable poses in the physical space during the user's walking. We rank the scores and choose the optimal target position and orientation to guide the user to the best pose. Since simulation experiments have been shown to be effective in many previous RDW studies, we also provide a method to simulate user walking trajectories and generate a dataset. Experiments show that our method outperforms multiple state-of-the-art methods in various environments of different sizes and spatial layouts.